2023
DOI: 10.1186/s12883-023-03467-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-life experiences with galcanezumab and predictors for treatment response in Turkey

Pınar Yalinay Dikmen,
Betül Baykan,
Derya Uludüz
et al.

Abstract: Background The complexity of clinical practice extends far beyond the controlled settings of trials, and there is a need for real-world studies aimed at identifying which patients will respond to anti-CGRP monoclonal antibodies in different countries. This study aimed to investigate the efficacy and safety of galcanezumab in treating migraine in a real-life setting in Turkey, as well as identify predictors of treatment response. Methods A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Several RWS are available all showing favorable results, some showing better results than the clinical trials ( 67–69 ). In a large RWS nearly 80.0% of the patients reported a decline in the frequency and in intensity of their headaches ( 70 ). Another study showed that galcanezumab was effective in chronic migraine regardless of medication overuse and poor responses were correlated with accompanying depression and everyday headache ( 68 ).…”
Section: Rational and Evaluation Of Cgrp Targeted Therapiesmentioning
confidence: 99%
“…Several RWS are available all showing favorable results, some showing better results than the clinical trials ( 67–69 ). In a large RWS nearly 80.0% of the patients reported a decline in the frequency and in intensity of their headaches ( 70 ). Another study showed that galcanezumab was effective in chronic migraine regardless of medication overuse and poor responses were correlated with accompanying depression and everyday headache ( 68 ).…”
Section: Rational and Evaluation Of Cgrp Targeted Therapiesmentioning
confidence: 99%
“…Galcanezumab, a humanized monoclonal antibody (mAb) targeting calcitonin gene-related peptide (CGRP)-mediated signaling cascade, is specifically developed for migraine prophylaxis in adults with EM and CM ( 15 , 16 ). Several studies have consistently shown the efficacy of galcanezumab in enhancing migraine outcomes, including improvements in functional and disability scores, all while maintaining a favorable safety and tolerability profile ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%